Ethnic Differences in the Association Between Pain and Social Support in Iraq and Afghanistan Veterans. Issue 11 (5th February 2020) - Herbert, Matthew S; Hernandez, Jeffrey; Dochat, Cara; Pittman, James O E; Afari, Niloofar
Abstract: Objective: Although past research has identified differences in pain between non-Latino white (NLW) and Latino persons, few studies have focused on the influence of social support. The purpose of the present study was to determine if the association between the number of social support sources and ratings of pain intensity and pain interference differed as a function of ethnicity. Design: Cross-sectional. Setting: Veterans Affairs San Diego Healthcare System Subjects: Participants were NLW (N = 389) and Latino (N   =   207) Iraq and Afghanistan veterans. Methods: Linear regression analyses were used to examine the interaction between ethnicity and number of social support sources on pain intensity and pain interference as measured by the Patient-Reported Outcomes Measurement Information System pain inventory. Results: The association between number of social support sources and pain intensity and interference significantly differed by ethnicity ( P  <   0.01 and P  =   0.01, respectively). Among NLW veterans, there was a significant negative association between number of social support sources and pain intensity. Among Latino veterans, there was a significant positive association between number of social support sources and pain intensity and interference. Conclusions: These findings suggest important differences between NLW and Latino Iraq and Afghanistan veterans in the association between social support and pain. Future research should examine ethnic differences in pain-specific support received from the social environment.